THЕ IMPОRTАNCЕ ОF USING INNОVАTIVЕ TЕCHNОLОGIЕS IN TЕАCHING FОRЕIGN LАNGUАGЕ - Abdusalomova, Farangis (Educational Research in Universal Sciences, 2024)
This article explores the modernization of foreign language education, highlighting the shift from traditional authoritarian teaching methods to student-centered, problem-based learning approaches. It emphasizes the importance of developing students’ competencies through interactive exercises, multimedia resources, and exposure to authentic language scenarios. The article also discusses the role of information technology in enhancing communication, facilitating personalized learning, and promoting cultural understanding. It concludes by advocating for the continuous adoption of innovative approaches to modernize the entire educational system.